Breastfeeding and Infant Growth: A Study of Weight and Length Gain in Malang, Indonesia - Parmasari, Wahyuni Dyah; Palupi, Marsella Tiara (Journal of Syiah Kuala Dentistry Society, 2025)
Every human has a growth process from the womb until adulthood. Growth is a process of quantitative change, such as a change in size, structure, and body organs. One of the factors that can affect growth is nutrition, which can be fulfilled by breastfeeding until two years. The anthropometric measures the children's growth according to their age, which will be adjusted to the KIA (Maternal and Child Health Book). It has four approaches of measurement, but this study only focuses on measuring weight gain and body length. This study aims to determine whether there is a relation between breastfeeding on babiess weight gain and body length at age 0-12 months in Kabupaten Malang. the method that is applied is Spearman's rank. The data in this study were classified into two categories, namely baby who is given complementary food and those without complementary food (MPASI). Baby without complemantary food showed that it does have relation between breastfeeding and baby growth (weight gain and body length) because of the significant values where = 0,027 and p = 0,037, which means that is smaller than 0,05 meanwhile, baby with complimantary food also have the same result because the significant values are = 0,037 and = 0,049, which means that is smaller than 0,05. This shows that babies who consume breast milk have the right levels for child growth, with or without complementary foods.